2013
DOI: 10.4172/2168-9849.1000108
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between HLA Typing and Different Diseases in IRAQ

Abstract: Human leukocyte antigen system is the major histocompatibility complex in humans, which includes several hundreds of genes located in a highly polymorphic region of chromosome 6 that encode for proteins critical for the immune system. HLA Class I antigens (A, B and C) transport and present peptides produced by degradation of proteins inside the cell like viral antigens, to CD8+ T cells, in addition to that the HLA Class I, carry also foreign or not-self antigens. Under normal conditions, these T -cell CD 8+ ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Thus, HLA typing can be used as a screening method to assess an individual's susceptibility to some autoimmune diseases. Furthermore, HLA typing can be used to help assess the prognosis, since it may be involved in the development and progression of the disease (5). The DNA typing analysis of this study revealed an increased rate of HLA-A*01, HLA-A*03, HLA-B*07, and HLA-B*38 alleles in dead cases and a powerful association with the mortality (P < 0.05) in our sampled Iranian population.…”
mentioning
confidence: 53%
“…Thus, HLA typing can be used as a screening method to assess an individual's susceptibility to some autoimmune diseases. Furthermore, HLA typing can be used to help assess the prognosis, since it may be involved in the development and progression of the disease (5). The DNA typing analysis of this study revealed an increased rate of HLA-A*01, HLA-A*03, HLA-B*07, and HLA-B*38 alleles in dead cases and a powerful association with the mortality (P < 0.05) in our sampled Iranian population.…”
mentioning
confidence: 53%
“…It was thought that these diseases could be brought on by a variety of racial, religious, and environmental factors. 8 Various efforts were devoted thereafter to launch a nationwide study on setting allelic and haplotypic HLA map and their correlation with diseases but regrettably, they were not successful. Iraq is among Arabian countries where consanguineous marriage is culturally the preferred type of marriage.…”
Section: Dear Editormentioning
confidence: 99%